Heritable disorders of collagen - Yeowell, Heather (Henry Stewart Talks, 2007)
Collagen biosynthesis, Collagen structural assemblies, Linkage of disorders to collagen mutations, Linkage of Ehlers-Danlos syndromes (EDS) to either collagen mutations or enzyme deficiencies, Kyphoscoliotic type (EDS VIA) and Lysyl Hydroxylase (LH) deficiency, Mutational analysis of LH1 gene, EDS VIB, LH isoforms, LH2 splicing
Updated at 2017/05/29